Biochemical engineering : a textbook for engineers, chemists and biologists. - Katoh, Shigeo, ....-; Yoshida, Fumitake, ....- (Weinheim : Wiley, 2009)
Biochemical engineering focuses on the design and construction of unit processes that involve biological organisms or molecules. It is increasingly taught as a separate discipline and as a supplementary option to chemical or biological engineering due to the similarities in both the background subject curriculum and problem-solving techniques. Its applications are to be found in the food, feed, pharmaceutical, biotechnology, and water treatment industries.